Re-Evaluation of Nicotinic Acetylcholine Receptors in Rat Brain by a Tissue-Segment Binding Assay - Wang, Mao H.; Yoshiki, Hatsumi; Anisuzzaman, Abu Syed M.; Uwada, Junsuke; Nishimune, Atsushi; Lee, Kung S.; Taniguchi, Takanobu; Muramatsu, Ikunobu (Frontiers in Pharmacology, 2011)
Nicotinic acetylcholine receptors (nAChRs) of the cerebral cortex and cerebellum of rats were evaluated by a radioligand binding assay, employing tissue segments, or homogenates as materials. [3H]-epibatidine specifically bound to nAChRs in rat cortex or cerebellum, but the dissociation constants for [3H]-epibatidine differed between segments and homogenates (187 pM for segments and 42 pM for homogenates in the cortex and 160 pM for segments and 84 pM for homogenates in the cerebellum). The abundance of total nAChRs was approximately 310 fmol/mg protein in the segments of cortex and 170 fmol/mg protein in the segments of cerebellum, which were significantly higher than those estimated in the homogenates (115 fmol/mg protein in the homogenates of the cortex and 76 fmol/mg protein in the homogenates of the cerebellum). Most of the [3H]-epibatidine binding sites in the cortex segments (approximately 70% of the population) showed high affinity for nicotine (pKi = 7.9), dihydro-β-erythroidine, and cytisine, but the binding sites in the cerebellum segments had slightly lower affinity for nicotine (pKi = 7.1). An upregulation of nAChRs by chronic administration of nicotine was observed in the cortex segments but not in the cerebellum segments with [3H]-epibatidine as a ligand. The upregulation in the cortex was caused by a specific increase in the high-affinity sites for nicotine (probably α4β2). The present study shows that the native environment of nAChRs is important for a precise quantitative as well as qualitative estimation of nAChRs in rat brain.